2015
DOI: 10.1186/s12891-015-0567-5
|View full text |Cite
|
Sign up to set email alerts
|

Is the state of health of rheumatoid arthritis patients receiving adequate treatment, predictable? - Results of a survey

Abstract: BackgroundA survey was conducted to evaluate whether a steady improvement in the quality of life of Rheumatoid Arthritis (RA) patients as frequently reported in clinical studies, does actually occur. The focus of this study laid on the personal perception of RA patients. How do patients who have been treated along accepted guidelines see the state of their health and their joint pain at different points in time?MethodsRA patients were asked to complete a questionnaire and return it to an opinion research centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…X-ray findings were suggestive of RA, but unusually, no symptoms to report and no tenderness of the affected joints. Joint pain affects the daily lives of the majority of patients with RA, even those established on treatment [ 9 ]. Cases of painless synovitis in RA are rare but have been reported and have been shown to follow a similar disease progression to those with pain [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…X-ray findings were suggestive of RA, but unusually, no symptoms to report and no tenderness of the affected joints. Joint pain affects the daily lives of the majority of patients with RA, even those established on treatment [ 9 ]. Cases of painless synovitis in RA are rare but have been reported and have been shown to follow a similar disease progression to those with pain [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 However, this frequency of visits may not always be possible due to specific barriers such as geographical and health-system-related constraints and, even in the case of high-quality care, patients' lives may not be predictable due to disease activity fluctuations. 21 Frequent remote patient monitoring could potentially lead to the early identification of disease flares, prioritisation of patients who may require a treatment review, and possibly reduced appointment frequency for those with stable disease. Evidence has shown that fluctuations in disease activity do have a direct effect on the destruction of joints.…”
Section: Key Messagesmentioning
confidence: 99%
“…Quality of life can change according to the environment and the experiences, as well as in response to certain diseases. 5 Pediatric Quality of life inventory version (pedsQL Generic Core Scale) Child -Report the PedsQL has 23 items and covers Physical, emotional, social, and school functioning and wellbeing. 6 We sought to measure the health-related quality of life of a group of children with juvenile idiopathic arthritis to reveal their main problems that hinder their wellbeing.…”
Section: Introductionmentioning
confidence: 99%